A Thematic Analysis of Yellow Leaves by M. R. Gohar - Ghulam Abbas; Hira Siddique; Ashir Khurshid (Review Journal of Social Psychology & Social Works, 2025)
Gohar is an emerging voice in Pakistani literature. He focuses on multiple issues and problems of Pakistani society. Hence, this study sought to make a thematic analysis of ten representative poems from Yellow Leaves by M. R. Gohar, focusing on their description of the Coronavirus epidemic that impact the psychological wellbeing. Through a qualitative, descriptive approach: poems were systematically sampled and the content analyzed in terms of themes. This study finds that Yellow Leaves is a rich literary exploration, which incorporates the author’s own personal experiences into broader stories of society in response to this global crisis. Gohar captures variety of themes so elegantly that we, the readers, can enjoy them and experience them all with our hearts. This research is of great importance for showing that literature plays a crucial part in both reflecting and forming the sense of shared interest characterizing collective consciousness during times crisis, as well as providing an excellent starting point from which to further examine this plethora.